Utilization of Cauliflower Stems and Leaves Powder in the Development of High Fibre Spent Hen Meat Cutlets - Kaur, Simranjeet; Goswami, Mayank; Kumar, Pavan; Mehta, Nitin; Sharma, Amit (Journal of Meat Science, 2022)
The present study was envisaged to develop high fibre spent hen meat cutlets by utilizing stems and leaves powder of cauliflower (CLSP) at four different levels viz. Control-0%, T1-2%, T2-4% and T3-6%, by replacing lean meat in the basic formulation. The developed meat cutlets were analyzed for various physicochemical, proximate, instrumental colour, texture and sensory attributes. Moisture, cooking yield, ash and fibre content recorded a significant (p
Keywords: Cauliflower stems and leaves powder; Cutlets; Fibre enrichment; Physicochemical attributes; Sensory attributes